An Insight into Immunological Therapeutic Approach against Cancer: Potential Anti-cancer Vaccines - Kohli, Arjun Singh; Sanyal, Somali; Kaushal, Radhey Shyam; Dwivedi, Manish (Current Genomics, 2025)
The development of a cancer vaccine comes with its complications and designing and developing a vaccine against foreign invaders such as bacterial and viral particles is not as complex and multi-faceted as the preparation of immunotherapy for host-infected cells which resemble our own body cells. The entire research and development framework of designing a vaccine for cancerous cells lies entirely on the remarkable aspect of notifying specific interactions and acclimatising the immune system. This review aims to compile the several fronts research-based methodology applies to in terms of developing a therapeutic, preventive or personalised vaccine for cancer. The approach lays focus on the identification and selection of targets for vaccine development which have come to light as immune biomarkers. Furthemore, significant aspects of personalised and precision vaccines and the fine line that runs between these approaches have also been discussed.
Keywords: Cancer